2017
DOI: 10.2147/copd.s144969
|View full text |Cite
|
Sign up to set email alerts
|

SIRT1 and FOXO1 mRNA expression in PBMC correlates to physical activity in COPD patients

Abstract: BackgroundPhysical activity (PA) is considered as one of the most important prognostic predictors in chronic obstructive pulmonary disease (COPD) patients. Longevity gene, SIRT1, is reported to be involved in the pathogenesis of COPD by regulating the signaling pathways of oxidative stress, inflammation, and aging. We hypothesize that SIRT1 and related genes are also associated with the benefits of PA in COPD patients.MethodsEighteen COPD outpatients were enrolled in this study, and their PA level was assessed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
18
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 39 publications
0
18
0
Order By: Relevance
“…The skeletal muscles play a pivotal role in the mechanical processes underlying breathing and movement. Previous studies in COPD patients revealed that lower skeletal muscle mass, assessed by the CSA of the quadriceps or ESM, contributes not only to breathlessness and poorer functional capacity, but also to worse prognosis [38][39][40]. Additionally, the ESM CSA values were significantly lower in COPD patients than in the smoking controls, and were associated with disease severity [18].…”
Section: Discussionmentioning
confidence: 97%
“…The skeletal muscles play a pivotal role in the mechanical processes underlying breathing and movement. Previous studies in COPD patients revealed that lower skeletal muscle mass, assessed by the CSA of the quadriceps or ESM, contributes not only to breathlessness and poorer functional capacity, but also to worse prognosis [38][39][40]. Additionally, the ESM CSA values were significantly lower in COPD patients than in the smoking controls, and were associated with disease severity [18].…”
Section: Discussionmentioning
confidence: 97%
“…21 In addition, evidence suggested that SIRT1 and FOXO1 mRNA expression levels in PBMCs correlate to physical activity in COPD patients. 22 We intend to explore more potential autophagyrelated genes of COPD in the future.…”
mentioning
confidence: 99%
“…FOXO1, a member of the forkhead-box O family, can act as a homeostasis regulator and coordinate responses to various environmental changes, including oxidative stress. 39 , 40 Liu et al 41 identified that AMPK alleviated endoplasmic reticulum stress in COPD through activation of FOXO1. In agreement with the study of Hueso et al, 42 FOXO1 expression of our analysis was decreased in COPD plasma compared with normal plasma, suggesting that miR-130b-5p-FOXO1 may participate in the pathogenesis of COPD through excessive oxidative stress.…”
Section: Discussionmentioning
confidence: 99%